New or rare Madagascar tiger beetles—24. Pogonostoma (Microgeniatum) signifemorale sp. nov. with revised key to species of the subgenus Microgeniatum Rivalier (Coleoptera: Cicindelidae) - Moravec, Jiří; Trýzna, Miloš (Zootaxa, 2021)
Pogonostoma (Microgeniatum) signifemorale sp. nov., based on a male holotype caught recently in the Ankarafantsika National Park (northwestern Madagascar), is described as new to science. The new species is immediately distinguished from other three hitherto known species of the subgenus Microgeniatum Rivalier, 1970, including a somewhat similar P. (Microgeniatum) infimum Rivalier, 1970. Consequently, a revised differential diagnosis and a revised key to species of the subgenus are presented in order to supplement the key and diagnosis in the monograph of the genus Pogonostoma Klug, 1835 by Moravec (2007). The male holotype is illustrated in colour photographs of its habitus and diagnostic characters with references to the illustrations of the other three species of the subgenus in the monograph of the genus (Moravec 2007). The habitat and ecology of the new species, as well as essential maps of known distribution of the subgenus, are also presented.